2020
DOI: 10.1155/2020/8082560
|View full text |Cite
|
Sign up to set email alerts
|

(-)-cis-Carveol, a Natural Compound, Improvesβ-Amyloid-Peptide 1-42-Induced Memory Impairment and Oxidative Stress in the Rat Hippocampus

Abstract: Alzheimer’s disease (AD) could be considered a multifactorial neurodegenerative disorder characterized by the accumulation of the β-amyloid-peptide (Aβ) within the brain leading to cognitive deficits, oxidative stress, and neuroinflammation. The present work was carried out to investigate the neuroprotective effect of (-)-cis-carveol (1% and 3%, for 21 days) against the β-amyloid-peptide 1-42- (Aβ1-42-) induced AD. Twenty-five rats were divided into five groups (n=5/group): the first group—control (sham-operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The spatial learning and memory of the rats were evaluated using a protocol of the radial arm maze (RAM) task described for the first time by Olton and Samuelson [ 50 ] and modified by Hritcu et al [ 51 ]. Our RAM was built from grey-translucent Plexiglass and consisted of 8 arms in size of 40 × 10 × 20 cm (L × l × h, numbered from 1 to 8) radially arranged around a circular arena with 20 cm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…The spatial learning and memory of the rats were evaluated using a protocol of the radial arm maze (RAM) task described for the first time by Olton and Samuelson [ 50 ] and modified by Hritcu et al [ 51 ]. Our RAM was built from grey-translucent Plexiglass and consisted of 8 arms in size of 40 × 10 × 20 cm (L × l × h, numbered from 1 to 8) radially arranged around a circular arena with 20 cm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Investigation of neuroprotective activity of (-)-cis-carveol against β-amyloid-peptide 1-42 (Aβ1-42)-induced AD demonstrated that it significantly improved memory deficits induced by Aβ1-42 and investigated using Y-maze and radial arm maze tests. Furthermore, it significantly decreased Aβ1-42-induced oxidative stress indicating an important candidate to decrease symptoms of AD (59). ISSN: 2321-3647 www.ajphr.com 19…”
Section: Neuroprotective Activitiesmentioning
confidence: 95%
“…In detail, most of the compounds were pushing the cases of early and intermediate time points to the I and IV quadrants, while minor speciation of alkenes limited the cases of the end point on the middle of the left side quadrants. Besides, the terpenes and terpenoids describing the early and intermediate samplings majorly were those famous for their strong antimicrobial activity, e.g., Thymol, beta-Phellandrene, and Thujol [25], while the VOCs describing the end point cases possess an anti-oxidant nature, e.g., p-Cymene [60], trans-3-(10)-Caren-2-ol [61], and p-Mentha-1(7),8(10)-dien-9-ol (cis-Carveol) [62]. Lastly, it is interesting to observe even that 4-acetyl-1-Methylcyclohexene, which is a major compound derived from D-Limonene oxidation but toxic for host cells [63], was not a descriptor of end point cases, meaning that it was depleted during fermentation and somehow converted by colonic bacteria.…”
Section: Time-dependent Discrimination Of Alkenesmentioning
confidence: 99%